Bicuculline-induced rhythmic EEG episodes: gender differences and the effects of ethosuximide and baclofen treatment - Matejovská, I; Velísková, J; Velísek, L (Epilepsia, 1998)
PURPOSE: There are gender differences in the expression of seizures. We tested rhythmic EEG episodes induced by low doses of bicuculline in rats for gender differences. To verify the validity of these discharges as a model of absence seizures in both male and female rats, we tested the antiabsence drug ethosuximide (ESM) and a gamma-aminobutyric acid (GABA(B))-receptor agonist, baclofen, which may exacerbate absence seizures. METHODS: Adult rats of both sexes were used. Under general anesthesia, EEG electrodes were implanted over frontal and occipital cortex, and some females were ovariectomized. After recovery, male, intact female rats, and female rats ovariectomized and ovariectomized rats with estradiol replacement were compared for occurrence of rhythmic EEG episodes (approximately 6 cycles/ s) induced by 2.5 mg/kg of bicuculline, s.c. Because of gender differences in sensitivity to bicuculline, further pharmacologic effects of ESM (125 and 250 mg/kg, i.p.) and baclofen (2 mg/kg, i.p.) were tested separately in male (3.0 mg/kg of bicuculline), and female (2.5 mg/kg of bicuculline) rats. RESULTS: After the identical dose of bicuculline, s.c., male and female rats differed in the incidence of rhythmic episodes and in the latency to onset of the first as well as the generalized episode. Female rats with natural or exogenous estrogens (but not ovariectomized rats) developed EEG episodes more often than did males, and this effect could be attributed to the presence of estrogens. ESM pretreatment suppressed the episodes, whereas baclofen enhanced their occurrence, as well as the total duration of episodes without gender-specific differences. CONCLUSIONS: The study demonstrates gender differences (related probably to the presence of circulating estrogens) in the susceptibility of rats to develop rhythmic EEG episodes induced by threshold doses of bicuculline. This activity has some features of an acute absence seizure model.
Keywords: Animals; Baclofen; Epilepsy; bikukulin; Ethosuximide; Female; Rats, Wistar; ženské pohlaví; absentní epilepsie; Ovariectomy; ethosuximid; baklofen; Sex Factors; Incidence; epilepsie; Male; incidence; Bicuculline; sexuální faktory; krysa rodu Rattus; zvířata; mužské pohlaví; ovarektomie; Epilepsy, Absence; Estradiol; Rats; estradiol; potkani Wistar